Development of Sīroh An-Nabawiyyah Learning Media in Fiqh Siroh Ramadhan Al-Buthi Through the Concept of NPT (Narative, Pedagological, and Theological) - Udin Supriadi; Mohammad Rindu Fajar Islamy (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to develop the Sīroh An-Nabawiyyah Learning Media Through the Concept of Fiqh Sīroh Ramadhan Al-Buthi based on NPT (narrative, pedagogical, and theological) with the support of historical visualization. In the dimension of modernity, globalization and technological acceleration have an effect on reducing the moral morality of the younger generation. According to the contemporary Muslim scholar Prof. Dr Muhammad Sa'id Ramadhan Al-Buthi in his work Fiqh As-Sīroh recommends that the younger generation must be friends with the figure of Rasulullah SAW as an ideal role model in all aspects. Every event that happened to Rasulullah, according to Al-Buthi has pedagogical values that can be implemented in the life of a Muslim, thus giving birth to a young generation who is religious and religious. In line with Al-Buthi, Prof. Dr. Ali Jum'ah, a senior scholar of Al-Azhar Egypt, recommended that the younger generation be trained to build the paradigm of "Rosulullah SAW as a father" meaning they must consider Rasulullah as an example and uswatun hasanah. this according to him can serve to improve their character education and religiosity. In line with the above, in the view of researchers, the problems related to juvenile delinquency can be bridged by handling them by bringing them closer to pedagogical stories from the life journey of Rasulullah SAW. Through a qualitative approach with a library review technique of primary data of the historical works of the Prophet Muhammad written by contemporary Muslim scholars Prof. Dr. Ramadhan Al-Buthi entitled Fiqh As-Sīroh, as for secondary data taken from other literature such as Ar-Rahīq Al-Makhtum, Dirāsah Tahlīliyyah Li Syahshiyati Ar-Rāsul Muhammad, Sīroh Ibn Hisham, Sīroh Ibn Ishaq. This research is expected to be able to produce the development of learning media based on pedagogical values, so that every event has learning and theological values and can be contextualized with current reality. The methods that will be applied in developing this media in every story of the Prophet's journey include: 1) Visualization of images of relevant objects, 2) Narrating events and stories, 3) Analysis and discussion discussions 4) Describing pedagogical values, and 5) Describing theological values.